2015
DOI: 10.1007/s12665-015-4248-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spring flooding on DOM characterization in a small watershed of the Hun River, China

Abstract: Potential water pollution derived from melting snow is a growing concern to watershed management in northern climates. For most small watersheds in the Hun River Basin, substantial portions of the annual load of pollutants such as organic matter, ammonia, phosphorus and metals come from snowmelt and early spring runoff. Thus, the annual spring flood is a real threat to the trophic state and water quality of Hun River. By three-dimensional fluorescence technology, the composition and characteristics of dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Dissolved organic matter (DOM) is an organic continuum or mixture with different structures and molecular weights, containing abundant biogenic elements such as carbon, nitrogen, and phosphorus [1][2][3]. Thus, DOM plays an important role in the control of transport, speciation, and bioavailability of carbon, nitrogen, and other elements in aquatic ecosystems by providing energy sources to microorganisms [4,5], demonstrating important functions in matter cycling in aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolved organic matter (DOM) is an organic continuum or mixture with different structures and molecular weights, containing abundant biogenic elements such as carbon, nitrogen, and phosphorus [1][2][3]. Thus, DOM plays an important role in the control of transport, speciation, and bioavailability of carbon, nitrogen, and other elements in aquatic ecosystems by providing energy sources to microorganisms [4,5], demonstrating important functions in matter cycling in aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, DOM can be used to effectively track terrestrial sources to aid in water quality management. However, research on the fluorescence spectral characteristics of DOM in freshwater has concentrated primarily on rivers [3,5], while the influences of catchment ecosystem in eutrophic agricultural reservoirs has received relatively less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that fluorescent dissolved organic matter (DOM) has received considerable attention as a useful method for evaluating and managing water quality in various aquatic systems [17][18][19][20][21]. First, because DOM is rich in biological elements, such as carbon, nitrogen, and phosphorus [22][23][24], it can provide energy for microorganisms, thus playing a crucial role in the transportation, speciation, and bioavailability of carbon, nitrogen, and other elements in aquatic ecosystems [25,26]. Therefore, DOM occupies a paramount role in the matter cycle of aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In the Jiulong River, Luo et al (2014) studied the dynamics of ammonia-oxidizing archaea and bacteria in relation to nitrification along simulated dissolved oxygen gradient in sediment-water interface of the river estuarine wetland. Peng et al (2015a) stated that potential water pollution derived from melting snow is a growing concern to watershed management in northern climates such as in Northeast China. For most small watersheds in the Hun River Basin, substantial portions of the annual load of pollutants such as organic matter, ammonia, phosphorus and metals come from snowmelt and early spring runoff.…”
mentioning
confidence: 99%
“…This seems an attractive practice for efficient waste treatment. Different aspects sludge treatment, such as reactivation and succession of microbial communities and fermentation, were investigated byPeng et al (2015a) andLiu et al (2015a), respectively. Nitrogen removal from waste water is an important issue for water quality improvement in China(Gao et al 2015a) and other countries (AlDwairi et al 2014;Cicchella et al 2014;Pascual Aguilar et al 2014).…”
mentioning
confidence: 99%